Parents' knowledge and awareness towards hand foot mouth disease in Malaysia: A survey in Selangor - Yogambigai Rajamoorthy; Ong Hooi Tin; Niazlin Mohd Taib; Subramaniam Munusamy; Abram Luther Wagner; Mudatsir Mudatsir; Aye Aye Khin; Samsul Anwar; Shaufique Fahmi Sidique; Harapan Harapan (Elsevier, 2022)
Background: Outbreaks of hand foot mouth disease (HFMD) is endemic in Malaysia and causes outbreaks and deaths amongst young children. The aim of this study was to assess the knowledge and awareness towards HFMD and their associated determinants among parents in Malaysia. Methods: A community-based cross-sectional study was conducted between January and March 2020 in Selangor state of Malaysia using a self-administered survey. The validated questionnaires were distributed to parents with children attending kindergartens in the nine districts of Selangor through multistage sampling. Logistic regression was used to estimate the differences in knowledge and awareness between groups and to identify their associated variables. Results: We received 690 participant responses of which 485 were included in the final analysis. We found that only 34.4% of parents had good knowledge and 78.1% had good awareness of HFMD. The multivariate analysis found that those who were working in the private sectors had lower odds of having good knowledge compared to those who were working in the public sectors, adjusted odds ratio (aOR): 0.59; 95%CI: 0.36-0.97. Compared to Malay, Malaysian Chinese and Malaysian Indian had lower odds of having good awareness with aOR: 0.48; 95%CI: 0.29-0.81 and aOR: 0.44; 95%CI: 0.23-0.83, respectively. Conclusion: Although parents' awareness was relatively high, they have poor knowledge on HFMD in particular to identify the symptoms of severe cases, basic treatment and preventive measures of HFMD. HFMD information needs to be communicated in a simplified language including in online communications to improve parents' knowledge and awareness of HFMD.